2019
DOI: 10.1021/acscatal.9b01789
|View full text |Cite
|
Sign up to set email alerts
|

A Career in Catalysis: Howard Alper

Abstract: Still going strong in his seventies, Professor Howard Alper continues to make an impact on chemistry internationally. This Account highlights some of his key scientific achievements in catalysis. What began as a fundamental interest in the chemistry of metal carbonyls and their activity modes, evolved into a versatile program addressing some of the most significant and challenging issues in catalysis. Using well-defined metal carbonyl complexes, he and his lab were able to make fundamental insights into divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 210 publications
0
9
0
Order By: Relevance
“…Transition metal-catalyzed carbonylation reaction represents one of the most powerful and useful methods for the synthesis of organic carbonyl compounds . In the traditional transition metal-catalyzed ionic carbonylation processes of alkyl halides, some competitive reactions such as β-hydride elimination and isomerization of organometallic species are often encountered.…”
mentioning
confidence: 58%
“…Transition metal-catalyzed carbonylation reaction represents one of the most powerful and useful methods for the synthesis of organic carbonyl compounds . In the traditional transition metal-catalyzed ionic carbonylation processes of alkyl halides, some competitive reactions such as β-hydride elimination and isomerization of organometallic species are often encountered.…”
mentioning
confidence: 58%
“…This group developed as well alkoxycarbonylations using high CO pressures, high temperature and long reaction times. 6 Furthermore, it was observed that these reactions were not operative under anhydrous conditions or with other catalysts such as Fe 3 (CO) 12 and [Rh(CO) 2 ] 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur-containing compounds have been discovered in numerous natural products and also figure among agrochemicals, pharmaceuticals, and functional materials. Among the commonly used heterocumulenes, isothiocyanates are easily available and have been used to construct diverse scaffolds of S-containing heterocycles by transition-metal-catalyzed cyclization of isothiocyanates. , The Pd-catalyzed cycloaddition of vinylethylene carbonates with isocyanates and photogenerated ketenes have been applied to form both five- and seven-membered heterocycles (Scheme ). Unlike previous Pd-catalyzed cycloaddition of isothiocyanates where the C–S bond is usually formed, formation of the C–N bond could be realized in the Pd-catalyzed decarboxylative cycloaddition of VECs with isothiocyanates.…”
Section: Introductionmentioning
confidence: 99%
“…Among the commonly used heterocumulenes, isothiocyanates are easily available and have been used to construct diverse scaffolds of S-containing heterocycles by transition-metal-catalyzed cyclization of isothiocyanates. , The Pd-catalyzed cycloaddition of vinylethylene carbonates with isocyanates and photogenerated ketenes have been applied to form both five- and seven-membered heterocycles (Scheme ). Unlike previous Pd-catalyzed cycloaddition of isothiocyanates where the C–S bond is usually formed, formation of the C–N bond could be realized in the Pd-catalyzed decarboxylative cycloaddition of VECs with isothiocyanates. Herein, we report an efficient synthesis of 1,3-oxazolidine-2-thiones by Pd-catalyzed [3 + 2] cycloaddition of vinylethylene carbonates with isothiocyanates.…”
Section: Introductionmentioning
confidence: 99%